Academic and Behavioral Outcomes in School-Age South African Children Following Severe Traumatic Brain Injury - Dollman, Aimee K.; Figaji, Anthony A.; Schrieff-Elson, Leigh E. (Frontiers in Neuroanatomy, 2017)
Background: Children who have sustained severe traumatic brain injuries (TBIs) demonstrate a range of post-injury neurocognitive and behavioral sequelae, which may have adverse effects on their academic and behavioral outcomes and interfere with school re-entry, educational progress, and quality of life. These post-TBI sequelae are exacerbated within the context of a resource-poor country like South Africa (SA) where the education system is in a somewhat precarious state especially for those from disadvantaged backgrounds. Objectives: To describe behavioral and academic outcomes of a group of school-aged SA children following severe TBI. Methods: The sample included 27 school-age children who were admitted to the Red Cross War Memorial Children's Hospital (RXH), SA, between 2006 and 2011 for closed severe TBI and who received intracranial monitoring. We collected behavioral data using the Child Behavior Checklist (CBCL) and the Behavior Rating Inventory of Executive Function (BRIEF) and academic information sourced from the BRIEF, CBCL, medical folders, and caregivers. Analyses include descriptive statistics and bivariate correlation matrices. Results: The descriptive results show that (1) more than half of the participants experienced clinically-significant behavioral problems across the CBCL scales, (2) the working memory BRIEF subscale appeared to be the most problematic subdomain, (3) two thirds of the sample were receiving some form of, or were in the process of being placed in, special needs education, (4) there was a three-fold increase in the use of special education services from pre- to post-injury, and (5) more than half (n = 16) of the sample repeated at least one grade after returning to school post-injury. Correlation analyses results suggest that children with increased externalizing behavioral problems and executive dysfunction are more likely to repeat a grade post-injury; and that children with executive dysfunction post-TBI are more likely to require some form of special educational services. Conclusion: While there is a vast amount of literature on pediatric TBI (pTBI) academic and behavioral outcomes, little literature exists on the pTBI population from the developing world and SA specifically. This is important to address given unique challenges that face the country and its educational system, and its implications for the management and care of children post-TBI.